Feasibility of the Study on the Development of the Stroke Center in Mohammad Hoesin Hospital Palembang in 2017 - Junaidi, A; Savitri, M (KnE Life Sciences, 2018)
Stroke is a disease that causes the most death and disability in adults. Early diagnosis and prompt and appropriate treatment provides excellent results. Besides that, the treatment of stroke patients in the stroke unit’s special room can also provide more significant results than treating them in an ordinary treatment room. This study discusses the factors involved in the development of the stroke center at Mohammad Hoesin Hospital. It is a qualitative research with a descriptive analytic design. Excavation information is carried out by document search, Focus Group Discussion (FGD) and Consensus Decision-making Group (CDMG). FGD implementation has involved all parties/units related to this stroke center program. As for CDMG, it is carried out with all levels of directors and medical committees to decide what decisions must be made so that the stroke center program can be run. The results of the study found several factors that became obstacles in the implementation of the stroke center program, among others, infrastructure, human resources, and policies on stroke service standards. The results of the study suggest making short-, mediumand long-term plans for the establishment of a stroke center at Mohammad Hoesin Hospital that would include infrastructure, human resources, and policies/standards needed for the stroke center to run optimally. Keywords: central stroke, CDMG